Electrochemical Transformation of Facet‐Controlled BiOI into Mesoporous Bismuth Nanosheets for Selective Electrocatalytic Reduction of CO2 to Formic Acid. Issue 20 (17th September 2019) - Wu, Dan; Liu, Jianwen; Liang, Yue; Xiang, Kun; Fu, Xian‐Zhu; Luo, Jing‐Li
Abstract: Mesoporous bismuth nanosheets are prepared through electrochemical transformation of (100)‐facet exposed BiOI. Theoretical modeling and calculations are used to simulate the in situ morphological transformation of BiOI into Bi. Mesoporous Bi nanosheets show superior electrochemical CO2 reduction performance. A faradaic efficiency of 95.9 % at −0.77 VRHE for the conversion of CO2 into formic acid, is achieved for the mesoporous Bi nanosheet catalyst compared with 93.8 % at −0.87 VRHE for the smooth Bi nanosheets. Tafel analysis and DFT calculations indicate that the electrochemical CO2 reduction on mesoporous Bi nanosheets is kinetically faster with a higher resistance to H2 generation than that on smooth Bi(001) nanosheets. The CO2 ‐to‐HCOOH pathway is preferred through formation of an *OCHO intermediate on the (012) and (001) planes of Bi. The mesoporous structure induces a more accessible interaction with CO2, which makes a predominant contribution to the enhanced performance compared with the subsequent CO2 activation on different facets of Bi. Abstract : Sheet dreams (are made of this) : Mesoporous bismuth nanosheets prepared by electrochemical transformation of (100)‐facet exposed BiOI displayed a faradaic efficiency of 95.9 % at −0.77 VRHE for the conversion of CO2 into formic acid. The mesoporous structure induces better interaction with CO2 and makes a predominant contribution to the enhanced performance compared with the subsequent CO2 activation on different facets of Bi.